2017
DOI: 10.1007/s00391-017-1220-8
|View full text |Cite
|
Sign up to set email alerts
|

Dementia care management in primary care

Abstract: The IPE programs for dementia should be expanded and must be widely implemented in order to assess the impact on collaborative practice. This study will provide the knowledge base for structuring IPE trainings developing educational agendas and adapting existing guidelines to improve collaborative dementia care in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 25 publications
1
24
0
8
Order By: Relevance
“…[ 24 ] Also, other collaborative care models employing a system-wide approach such as the Aging Brain Care Medical Homes in the US and the German Delphi-MV study, have shown positive results. [ 2 , 22 , 25 , 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Also, other collaborative care models employing a system-wide approach such as the Aging Brain Care Medical Homes in the US and the German Delphi-MV study, have shown positive results. [ 2 , 22 , 25 , 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…To address patients’ and caregivers’ complex healthcare needs, several collaborative care models have been published in the last decade 8–11. These models are characterized by interprofessional teams, multicomponent interventions, and shared decision-making between healthcare professionals and patients as well as their caregivers 12. Previous studies have performed comprehensive patient-centered assessments of PLWD and their care partners, including the patient’s function, behavior and health status, and their challenges or unmet needs 9,10.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies throughout the world have reported the need for special, broad-scale, and regular training programs for GPs (Koch et al ., 2010b; Veneziani et al ., 2016; Dreier-Wolfgramm et al ., 2017). The importance of training cannot be emphasized enough to achieve higher quality dementia care.…”
Section: Discussionmentioning
confidence: 99%
“…Training and support for GPs may change their attitude that they have little to offer to patients living with dementia and to their relatives (Downs, 1996). Several studies confirm that GPs’ training should be practical, evidence-based and relevant, as well as tailored to their special needs: take into account their maturity, using individualized methods and include interprofessional education (Iliffe et al ., 2002; Dreier-Wolfgramm et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%